Larangan Bid’ah dalam Kitab Arbain Nawawi:: Analisis Hadis Nabi Tentang Larangan Melakukan Perbuatan Bid’ah dan Implementasinya Pada Kaidah Uluhiyyah - Irodat, Ahsan (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2023)
The Book of Hadith Arba'in is a work written by a great scholar, who has a high reputation among Muslims, namely Imam Nawawi. In the book of Arba'in there are also several other priests such as Al-Ajurri, Al-Baihaqi, Ash-Shabuni, Al-Hakim, Ad-Daruquthni, Ath-Tabari, As-Suyuthi, Ibn Hajar Al-Asqalani and in addition to those who number up to dozens of books of Arbain. And the book of arba'in is already very widely known and fragrant until now. The basis of this book is